Papain-based gel for biochemical caries removal: influence on microtensile bond strength to dentin - Evandro Piva; Fabrício Aulo Ogliari; Rafael Ratto de Moraes; Felipe Corá; Sandrina Henn; Lourenço Correr-Sobrinho (Sociedade Brasileira de Pesquisa Odontológica, 2008)
This study investigated the influence of a papain-based gel (Papacárie) for chemo-mechanical caries removal on bond strength to dentin. Human molars were assigned to the following groups: Group 1: sound teeth were flattened to expose dentin; Group 2: after flattening of surfaces, the papain-based gel was applied on the sound dentin; Group 3: overlying enamel from carious teeth was removed and mechanical excavation of dentin was conducted; Group 4: chemo-mechanical excavation of carious dentin was conducted using the papain-based gel. The Prime&Bond NT or Clearfil SE Bond adhesive systems were used for restorative procedures. A microtensile bond strength test was performed, and the modes of failure were determined under SEM. The data were submitted to two-way ANOVA and Tukey's test (p < 0.05). No significant differences were observed between the sound dentin groups. For both excavation methods, Clearfil presented a significantly higher bond strength than Prime&Bond NT. Also, for Clearfil, the mechanically excavated samples disclosed a significantly higher bond strength than the chemo-mechanically ones. For Prime&Bond NT, no significant differences were detected between the excavation methods. Predominance of mixed failures for the sound substrate and of adhesive failures for the carious dentin one was detected. The bond strength to carious dentin of the self-etching system was negatively affected by chemo-mechanical excavation using the papain-based gel.